Spectral Domain Optical Coherence Tomography in Macular Diseases - Meyer, Carsten H.; Saxena, Sandeep; Sadda, SriniVas R.; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2017)
This book aims to build concepts and create a solid foundation in the field of optical coherence tomography (OCT) for the general ophthalmologists as well as for the resident trainees and fellows. The chapters are written by leading international authorities in a style comprehensible to a broad audience. Numerous clinical pictures and SD-OCT scans help elucidate various clinical entities.OCT is the optical analog of ultrasound imaging and has emerged as a powerful imaging technique that enables non-invasive, in-vivo, high-resolution, cross-sectional imaging in retinal tissue. A new generation spectral domain optical coherence tomography (SD-OCT) technology has now been developed, representing a quantum leap in resolution and speed, achieving in vivo optical biopsy. i.e. the visualization of tissue architectural morphology in situ and in real time. This book encompasses the role of SD-OCT in both medical and surgical macular disorders. The book is meant coherent and comprehensive for both vitreoretinal specialists as well as general ophthalmologists.
Optical coherence tomography: Basic principles of image analysis -- Normal Macula: Focus on IS-OS junction, external limiting membrane and choroidal thickness -- Diabetic Macular Edema -- Retinal Vein Occlusion -- Retinal Artery Occlusion -- Dry Age-related Macular Degeneration -- Wet Age-related Macular Degeneration -- Polypoidal Disease -- Optical Coherence Tomography in Age-related Macular Degeneration Pharmacotherapy -- Juxtafoveal Telangiectasia -- Central Serous Chorioretinopathy -- Idiopathic Epiretinal membranes -- Vitreomacular Traction Syndrome -- Idiopathic Macular Hole -- Surgery for Choroidal Neovascular Membrane and Macular Translocation -- Macula after Retinal Detachment Surgery -- Myopic Foveoschisis -- Retinal Degenerations and Dystrophies -- Retinal and Choroidal Inflammation -- Optic Disc Pit Maculopathy -- Retinopathy of Prematurity -- Posterior Segment Trauma -- Ocular Oncology -- Miscellaneous Retinal Disorders -- Three Dimensional Imaging in Spectral Domain Optical Coherence Tomography -- Intraoperative OCT -- Ultra High Resolution OCT .
Keywords: Medicine; Public health; Ophthalmology; Surgery; Medicine & Public Health; Ophthalmology; Public health; Surgery